Respuesta :

Answer:

Part 1) [tex]f(125)=6[/tex]

Part 2) [tex]f(-64)=-3[/tex]

Step-by-step explanation:

we have

[tex]f(x)=\sqrt[3]{x} +1[/tex]

Part 1) Find f(125)

we know that

f(125) is the value of the function f(x) when the value of x is equal to 125

so

For x=125

substitute in the function

[tex]f(125)=\sqrt[3]{125} +1[/tex]

Remember that

[tex]125=5^{3}[/tex]

substitute

[tex]f(125)=\sqrt[3]{5^{3}} +1[/tex]

Applying the power of rule

[tex]\sqrt[3]{5^{3}}=(5^{3})^{\frac{1}{3}}= (5)^{3*\frac{1}{3}}=5[/tex]

substitute

[tex]f(125)=5 +1=6[/tex]

Part 2) Find f(-64)

we know that

f(-64) is the value of the function f(x) when the value of x is equal to -64

so

For x=-64

substitute in the function

[tex]f(-64)=\sqrt[3]{-64} +1[/tex]

Remember that

[tex]-64=-4^{3}[/tex]

substitute

[tex]f(-64)=\sqrt[3]{-4^{3}} +1[/tex]

Applying the power of rule

[tex]\sqrt[3]{-4^{3}}=(-4^{3})^{\frac{1}{3}}= (-4)^{3*\frac{1}{3}}=-4[/tex]

substitute

[tex]f(-64)=-4 +1=-3[/tex]